'One foot in the grave': pregnancy and folk culture in recent Russian films. (2nd January 2022) - Kaminer, Jenny
ABSTRACT: This article focuses on two recent Russian films – Vasilii Sigarev's Living (2012) and Natasha Merkulova and Aleksei Chupov's The Man who Surprised Everyone (2018) – that exploit the multivalent potential of the pregnant body. Both films enlist the symbolism with which Russian traditional culture has infused that body to create complex, nuanced cinematic depictions of the porousness between the realm of the living and that of the dead. The folk symbolism of pregnancy facilitates the directors' subtle critiques of contemporary Russian society, including its cynicism; casual, ubiquitous violence; and rigid gender hierarchies. These films highlight the pregnant woman's destabilising potential, one that challenges the Russian state's increasingly fervent incursion into the intimate realm separating life and death. They also prompt us to recall that feminist thinkers have turned to the pregnant body as a source of insight. With her challenge to the notion of a singular, unified body, the pregnant woman points to new philosophical models of the self – possibilities that have yet to be explored fully on screen, but towards which the two contemporary Russian films discussed in this essay may point.